Non‐Reciprocity, Metastability, and Dynamic Reconfiguration in Co‐Assembly of Active and Passive Particles - Ahmed Al Harraq; Ruchi Patel; Jin Gyun Lee; Ope Owoyele; Jaehun Chun; Bhuvnesh Bharti (Advanced Science)
Abstract Living organisms often exhibit non‐reciprocal interactions where the forces acting on the objects are not equal in magnitude or opposite in direction. The combination of reciprocal and non‐reciprocal interactions between synthetic building blocks remains largely unexplored. Here, out‐of‐equilibrium assemblies of non‐motile isotropic passive and metal‐patched motile active particles are formed by overlapping bulk interactions with directed self‐propulsion. An external alternating current (AC) electric field generates concurrent dipolar and induced‐charge electrophoretic forces between the particles which are evaluated using microscopy. The interaction force measurements allow to determine the degree of reciprocity in interactions, which is tunable by designing the active particle and its trajectory. While linearly‐propelled active particles evade assembly with passive particles, helically propelled active particles form active‐passive clusters with dynamic reconfiguration and long‐lived metastability. Large clusters display programmable fluctuations and reconfigurability by controlling the fraction of active particles. The study establishes principles of integrating reciprocal and non‐reciprocal interactions in guided colloidal assembly of reconfigurable metastable structures.